PENGARUH KONDISI KEUANGAN PERUSAHAAN TERHADAP TINGKAT PENGEMBALIAN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DALAM BURSA EFEK INDONESIA - Paryanto Paryanto; N. Dicky Sumarsoso (JURNAL ILMIAH EDUNOMIKA, 2018)
This study aims to determine the effect of variable price book value, price earnings ratio, earnings per share and dividend pay out ratio on stock returns (stock returns) on manufacturing companies listing on the IDX for the 2014-2016 period. In this study, researchers used purposive sampling and obtained a sample of 72 samples. From the sample obtained, the writer uses multiple linear regression test to explain the relationship between these variables. The result stated that 18.2% of stock returns (stock returns) were influenced by price book value, price earnings ratio, earnings per share and dividend pay out ratio, the remaining 81.8% was influenced by other variables. Partial testing succeeded in proving price book value, earning per share and dividend pay out ratio had a significant effect on stock returns, while price earning ratio did not significantly influence stock returns. While testing simultaneously shows price book value, price earnings ratio, earnings per share and dividend pay out ratio has a significant effect on stock returns. Keywords: price book value, earnings per dividend share pay out ratio stock return.